The excretion of zopiclone into breast milk. - Matheson, I (1990)
1. The excretion of zopiclone into breast milk was studied in 12 lactating women in the early postpartum period following the oral administration of a single zopiclone tablet (7.5 mg). 2. The milk/plasma AUC ratio of zopiclone was 0.51 +/- 0.09 (mean +/- s.d.). Individual mean milk/plasma concentration ratios of zopiclone showed significant interindividual variation (range 0.41-0.70). 3. A comparison of pharmacokinetic parameters in the postpartum women with those reported previously in non-pregnant women, showed significantly higher Cmax values in the lactating mothers; tmax occurred later in milk than in maternal plasma. 4. Assuming a daily milk intake of 0.15 l kg-1 and 100% absorption the average infant dose of zopiclone in milk would be 1.4% of the weight adjusted dose ingested by the mother.